Bullying the Brain? Longitudinal Links Between Childhood Peer Victimization, Cortisol, and Adolescent Brain Structure - du Plessis, Mieke R.; Smeekens, Sanny; Cillessen, Antonius H. N.; Whittle, Sarah; Güroǧlu, Berna (Frontiers in Psychology, 2019)
Background Childhood peer victimization is a stressful life experience associated with long-lasting adverse psychological consequences. While there is some evidence that victimization is associated with alterations in brain function, little is known about effects on brain structure. This study explored the relationships between childhood peer victimization, cortisol, and adolescent ventrolateral prefrontal cortex (vlPFC) structure in a sample of healthy children. Methods A total of 50 (Mage = 9.29 years at baseline) children participated in this longitudinal study. We examined whether diurnal cortisol levels (assessed at baseline) moderated the link between children’s self-reported peer victimization (assessed at baseline) and vlPFC surface area, gray matter volume, and thickness five years later. Results For boys, cortisol levels moderated the association between victimization and brain structure. For boys with a low daily cortisol output (assessed as area under the curve; AUC), high victimization was associated with a smaller right vlPFC surface area, and for boys with a high AUC, high victimization was associated with a larger right vlPFC surface area. In addition, for boys with a steeper diurnal slope, high victimization was associated with a smaller right vlPFC surface area, and for boys with a low flatter diurnal slope, high victimization was associated with a larger right vlPFC surface area. Conclusions These results indicate the differential influence of cortisol on the relationship between victimization and brain structure. Findings suggest that victimization may have differential effects on brain development in boys who are more versus less biologically sensitive to stress.